Identical longevity phenotypes are characterized by different patterns of gene expression and oxidative damage. - Arking, R.; Burde, V.; Graves, K.; Hari, R.; Feldman, E.; Zeevi, A.; Soliman, S.; Saraiya, A.; Buck, S.; Vettraino, J.; Sathrasala, K. (Experimental Gerontology, 2000)
Some years ago we applied simultaneously an identical regime of selection for late-life reproduction to several normal-lived sister lines (Ra and Rb) so as to produce several selected long-lived sister lines (La and Lb). The long-lived La and Lb sister lines had statistically identical longevity phenotypes and paraquat resistance phenotypes; however, we noticed some statistically different responses of the two strains at the biochemical level. Extensive work with the La strain showed that transcriptional alterations in antioxidant gene expression are robustly associated with its extended longevity. We decided to critically test the assumption of phenotypic equivalence by subjecting the Lb strain to the same series of molecular assays as was the La strain. The two sister strains are characterized by significantly different mechanisms and patterns of antioxidant gene expression, antioxidant enzyme activity, and oxidative damage. We find that the Lb strain appears to depend on the transcriptional activation of different genes than does the La strain, and on a post-translational up-regulation of at least one other antioxidant defense gene. The phenotypic equivalence observed at the organism level need not hold at the molecular genetic level. This finding suggests that there is more than one molecular mechanism by which antioxidant defense genes can bring about an increased resistance to oxidative stress. The theoretical and empirical implications of these findings are discussed.